Social Factors Predict Distress Development in Adults With Pre-existing Mental Disorders During the Coronavirus Disease 2019 Pandemic - Konrad, Annika C.; Förster, Katharina; Kurtz, Marcel; Endrass, Tanja; Jauk, Emanuel; Kanske, Philipp (Frontiers in Psychology, 2022)
Physical distancing measures during the coronavirus pandemic are associated with increased psychological distress, especially in people with mental disorders. We investigated which social risk and resilience factors influence distress over time in people with pre-existing mental disorders. We conducted a longitudinal online survey with weekly follow-ups between April and July 2020 (n = 196 individuals with, and n = 545 individuals without pre-existing mental disorders at baseline). Our results show that individuals with, but not those without pre-existing mental disorders displayed higher distress levels when social resources and empathic disconnection are low and perceived social isolation is high. The distress development differed between participants with and without pre-existing mental disorders depending on their level of social resources, empathic disconnection, and perceived social isolation. These findings offer specific information for targeted social interventions to prevent an increase in incidence of mental disorders during physical distancing measures.